NEUROPSYCHOLOGICAL AND PSYCHOMOTOR SYMPTOMS IN DEPRESSIVE PATIENT AT THE BEGINNING AND END TREATMENT (Fiep Bulletin - online, 2011)
Introduction: Major depressive disorder is characterized by symptoms which interfere within the normal activities of the patient, impairing their social, occupational, relational, and psychomotor performance, and it has a high prevalence in the world population. Objective and methodology: This paper aims to report the use of the "Catalogue of Neuropsychological impairments for adults – SZC" (Schlindwein-Zanini and Cruz) as a tool to detect neuropsychological disturbances in major depressive disorder in a 43-year-old female patient in early psychological treatment associated with the evaluation by Motor Development Scale (Rosa Neto, 2002). Conclusion: The SZC has proved to be useful in the detection of neuropsychological deficits in depressive disorders at different stages of the treatment. Through MDS (Motor Development Scale) psychomotor changes with depressive disorder have also been evident, especially in the area of balance.
Keywords: depression; neuropsychology; psychomotricity